Pomodori e pesticidi. (In)giustizia alimentare, sanitaria e ambientale nelle Regioni ultraperiferiche: il caso di Mayotte - Paola Schierano (Archivio Antropologico Mediterraneo)
Through this paper we intend to offer a contribution to the debate on food and environmental security and sustainability in the European Outermost regions, so as to illustrate the not-so-apparent linkages between departmentalisation, socio-economic inequalities and food and environmental insecurity. Historically known as the “garden” of the Comoro Islands, Mayotte is the only island of the Comoro archipelago to have rejected independence, preferring to it a full – albeit turbulent – integration to France. Because of its relative richness, Mayotte represents nowadays the main destination of illegal immigration in the South-West Indian Ocean. Some of the most frequent activities to be carried out by migrants – mainly from the Comoro and Madagascar – stand out the cultivation and street vending of fruit and vegetables, especially tomatoes. According to a survey promoted by the Direction of Food, Agriculture and Forest (DAAF), the vast majority of tomatoes sold by street vendors presents very high rates of dimethoate, an extremely neurotoxic insecticide, banned in Europe in 2016. Through the example of the “forbidden tomatoes” of Mayotte, this paper aims to explore the entanglement between socio-economic inequalities – generated and/or compounded by the departmentalisation process – and the resulting food and environmental insecurity.